Entrepreneurship Training for Mitigating Unemployment in Nigeria: How have the Tertiary Institutions Fared? - Eneji, Rosemary I; Nwbagbara, E. N; Kati, Kati George (Journal of Social Economics Research, 2020)
The increasing unemployment in Nigeria is one of the social problems contributing to abject poverty, crime and other civil vices plaguing the country today. Although the public and private sectors have made some efforts in addressing the problem, available current statistics show that both sectors lack the capacity to solely employ the entire manpower base of the country. Considering the potential of entrepreneurial training for reducing unemployment, the Nigerian government through the National Universities Commission (NUC) introduced entrepreneurial education as a compulsory course in various higher institutions. In this study, we aimed to ascertain the extent to which these institutions have implemented entrepreneurial education for mitigating unemployment in Nigeria, using the University of Calabar as a case study. A combination of structured questionnaires, titled students’ Opinion Questionnaire and review of extant literatures and theoretical framework, was used for the study. The resulting data showed that the tertiary institutions have not significantly contributed to mitigating unemployment through entrepreneurial education, judging from the low students’ acquisition of entrepreneurial skills, their limited exposure to business opportunities and difficulty in sourcing funds to ensure utilization of any acquired skills after graduation.